For healthy animals - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Department of Veterinary Medicine of the Prince Leopold Institute of Tropical Medicine in Antwerp, Belgium is offering a diploma course on tropical animal health and production (CIPSAT) for veterinarians, biologists and agronomists. The course...